1999
DOI: 10.1117/12.373521
|View full text |Cite
|
Sign up to set email alerts
|

<title>Case for predictable media quality in networked multimedia applications</title>

Abstract: Shared networks are now able to support a wide range of applications, including real-time multimedia. This has led the networking community to consider a wider range of network Quality of Service (QoS) guarantees and pricing schemes. To date, the QoS required by networked multimedia applications has been described in terms of technical parameters. We argue that, in order to maximize the realized quality of any network, the QoS requirements of networked multimedia applications should be based on the value that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Consequently, other metrics have been developed and incorporated into the ITU recommendations. The single stimulus continuous quality evaluation (SSCQE) [4,8] [3] also used a slider with which the user could continuously rate quality. However , they concluded that the method is too involved for users performing a real task.…”
Section: Background Perceived Quality Of Service (Qos)mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, other metrics have been developed and incorporated into the ITU recommendations. The single stimulus continuous quality evaluation (SSCQE) [4,8] [3] also used a slider with which the user could continuously rate quality. However , they concluded that the method is too involved for users performing a real task.…”
Section: Background Perceived Quality Of Service (Qos)mentioning
confidence: 99%
“…[7], we adapt psychophysical methods and gradually increase and decrease video quality within a single clip to identify the exact level at which quality becomes acceptable or unacceptable to these users. (3) We investigate the effects of varying both frame rate (fps) and frame quality (quantization scale) on acceptability. Furthermore, whilst previous studies have collected only subjective responses, we (4) record participants' eye movements (Study 1) to determine what aspects of the video are actually looked at.…”
Section: Introductionmentioning
confidence: 99%
“…According to Festinger's [1957] dissonance theory, people seek, notice and interpret data that fits their attitudes and avoid information that is inconsistent with their attitudes or choices [14]. Attitudes affect multimedia quality evaluations, as was shown in an experiment by Bouch and Sasse [4] in which participants with low expectancies gave high ratings, and participants with high expectancies were more critical in their evaluations.…”
Section: Emotion and Attitude In Perceptionmentioning
confidence: 90%
“…In continuous assessment, participants express their quality evaluation moving the slider on a graphical 5-point labeled MOS scale while watching the content. It has been used to assess the excellence of video and audiovisual quality [50][51][52]. Similarly to ACR and QoP, the acceptance threshold is hard to locate on this scale.…”
Section: Quality Evaluation Methodsmentioning
confidence: 99%